COVID-19 and dental distance-based education: students’ perceptions in an Italian University - Di Giacomo, Paola (BMC Med Educ, 2021)
BACKGROUND: The aim of the study was to analyze the perception of dental faculties students regarding the complete transition to distance-based education (DE) and the adaptation of this educational strategy, due to Covid-19 pandemic. A questionnaire to be completed anonymously was submitted online to students attending the faculties of Dentistry and Oral Hygiene at Sapienza, University of Rome, after the end of distance lessons. The collected data were processed statistically, providing descriptive data and analysis of correlation of the most significant parameters, using Chi-squared test, Cramér V and Pearson φ(2), Goodman and Kruskal’s γ and λ and Kendall’s τb. The level of statistical significance was p < 0.05. RESULTS: A total of 314 students participated in the survey. The overall level of satisfaction on a ten- point scale was 5.39 ± 2.59 for Oral Hygiene students and 6.15 ± 2.98 for Dentistry students. The most common complaints were the lack of a structured online curriculum, less interaction with professors and a lower level of attention. On the basis of the responses, scored using Likert-type Scale, oral Hygiene students reported statistically higher level of physical fatigue(p = 0.0189), a lower level of attention (p = 0.0136) and of the quality and quantity of acquired knowledge during distance education (p = 0.0392), compared to Dentistry students. Level of perceived stress and quality and quantity of acquired knowledge (γ = 0.81 and τb =0.56) and quality and quantity of acquired knowledge and fear of a decrease in knowledge (γ = 0.76 and τb =0.54) are associated variables. CONCLUSION: Students’ feedback is essential to solve the key issues emerged from the questionnaire. New educational models should be define in order to ensure that distance education could be effective, meeting the learning needs of the students, and could not be a merely “online shift” of traditional methods, used as an alternative of live education. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12909-021-02840-3.